PENGARUH NON PERFORMING LOAN (NPL), LIKUIDITAS DAN RENTABILITAS TERHADAP RASIO KECUKUPAN MODAL - Anjani, Dewa Ayu; Purnawati, Ni Ketut (E-Jurnal Manajemen, 2014)
The research aims to know the influence non performing loan, loan to deposit ratio, return on equity and  net interest margin to capital adequacy ratio in partial. The banking sector in Indonesia stock exchange period 2009-2011 is this research case studies. T-test was used in the multiple linear regression analysis technique. Research described that NPL have no significant influence to the CAR. LDR have negative significant influence to the CAR. ROE have negative significant influence to the CAR. NIM have positive significant influence to the CAR.
Keywords: non performing loan; loan to deposit ratio; return on equity; net interest margin; capital adequacy ratio